Higher Education and the Labour Market - Adina Moise – Titei (Ovidius University Annals: Economic Sciences Series, 2016)
The purpose of the present paper is to highlight the importance of qualification for the economyand especially to analyse the impact of increasing the general level of education on theemployment rate. Therefore, after a short presentation of the situation of tertiary education at EUlevel, we put in correlation two indicators: the employment rates for tertiary education and thenumber of students in tertiary education. The results show us that between them it is a negativecorrelation, but the relationship is not strong enough.